2007
DOI: 10.1373/clinchem.2006.077339
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biosensor–Based Analytic Device for the Detection of Anti–Double-Stranded DNA Antibodies

Abstract: Background:Patients with systemic lupus erythematosus (SLE) develop a wide variety of serologic manifestations, including double-stranded DNA autoantibodies (anti-dsDNA). The determination of the potentially pathogenic autoantibodies is diagnostically relevant. Methods: We developed a novel surface plasmon resonance (SPR) biosensor chip for studies of dsDNA and anti-dsDNA binding. A synthetic oligonucleotide was coupled to biotinylated human transferrin, hybridized with the complementary antistrand, and ligate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Also, our SPR biosensor marks a new approach with promising possibilities. 10,14 The Farr assay is still considered as the gold standard for clinicians. Advantageous is the high specificity for diagnosing SLE and the discrimination from other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our SPR biosensor marks a new approach with promising possibilities. 10,14 The Farr assay is still considered as the gold standard for clinicians. Advantageous is the high specificity for diagnosing SLE and the discrimination from other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There were also reports on a novel surface plasmon resonance biosensor chip analytic method (29) and an innovative quantitative electrochemical detection of anti-DNA antibodies (30). Just recently, a novel method using electrophoretic mobility shift assay was reported by Keyhani et al (31), which showed in vivo and in vitro detections of a complex formation between plasma membrane DNA and IgG from SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) has been successful so far for many reasons include the easy cleaning and the infinite reuse of the sensor. Thiol based monolayers are normally grafted to gold or silver surfaces allow specific detection of DNA [Buhl, et al, 2007] or organic pollutants [Farré, et al, 2007& Mauriz, et al, 2006 and pathogens [Chah & Zare, 2008] with coupling of DNA and antibodies. A significant improvement has been achieved with the formation of more multifaceted sensing architectures using the assembly of nanoparticles onto the gold surface of the SPR: the signal amplification caused by the coupling of the SPR signal with the localized surface plasmons of the metal or semiconductor nanoparticles (Fig.…”
Section: Biodetection Based On Organic Monolayers On Surfacesmentioning
confidence: 99%